Infrastructure for 3D Modeling of Historical Fountains in Istanbul with GIS-Based Procedural Approach - Şenyurdusev, Güçlü; Dogru , Ahmet Ozgur (Geomatics and Environmental Engineering, 2024)
Along with the concepts of “smart city” and “digital twin,” the 3D (threedimensional) city models have started to be used as a basis for many studies that have been carried out in recent years. The most important and basic components of 3D city models are the structures that are located in the cities. However, some small structures of historical importance are within the category of the buildings in a city but are often not as large as a building. Historical fountains are some of these structures. For this reason, modeling with existing 3D city model-production methods is a little more complicated and requires local measurements and detailed modeling studies. As a result, this study has designed a database scheme design in which the historical city wall fountains in Istanbul can be stored in a spatial database and modeled in three dimensions (with procedural modeling when necessary). In addition, the conveniences that this infrastructure will provide in the production of 3D structure models and some difficulties that were encountered during these studies are also discussed and examined.